Effects of Healthcare Organization Actions and Policies Related to COVID-19 on Perceived Organizational Support Among U.S. Internists: A National Study. Issue 3 (May 2022) - Sonis, Jeffrey; Pathman, Donald E.; Read, Susan; Gaynes, Bradley N.; Canter, Courtney; Curran, Patrick; Jones, Cheryl B.; Miller, Thomas
SUMMARY: Goal: Perceived organizational support (POS) may promote healthcare worker mental health, but organizational factors that foster POS during the COVID-19 pandemic are unknown. The goals of this study were to identify actions and policies regarding COVID-19 that healthcare organizations can implement to promote POS and to evaluate the impact of POS on physicians' mental health, burnout, and intention to leave patient care. Methods: We conducted a cross-sectional national survey with an online panel of internal medicine physicians from the American College of Physicians in September and October of 2020. POS was measured with a 4-item scale, based on items from Eisenberger's Perceived Organizational Support Scale that were adapted for the pandemic. Mental health outcomes and burnout were measured with short screening scales. Principal Findings: The response rate was 37.8% ( N = 810). Three healthcare organization actions and policies were independently associated with higher levels of POS in a multiple linear regression model that included all actions and policies as well as potential confounding factors: opportunities to discuss ethical issues related to COVID-19 ( β (regression coefficient) = 0.74, p = .001), adequate access to personal protective equipment ( β = 1.00, p = .005), and leadership that listens to healthcare worker concerns regarding COVID-19 ( β = 3.58, p < .001). Sanctioning workers who speak out on COVID-19 safety issues or refuse pandemic deployment was associated with lower POS ( β = –2.06, p < .001). In multivariable logistic regression models, high POS was associated with approximately half the odds of screening positive for generalized anxiety, depression, post-traumatic stress disorder, burnout, and intention to leave patient care within 5 years. Applications to Practice: Our results suggest that healthcare organizations may be able to increase POS among physicians during the COVID-19 pandemic by guaranteeing adequate personal protective equipment, making sure that leaders listen to concerns about COVID-19, and offering opportunities to discuss ethical concerns related to caring for patients with COVID-19. Other policies and actions such as rapid COVID-19 tests may be implemented for the safety of staff and patients, but the policies and actions associated with POS in multivariable models in this study are likely to have the largest positive impact on POS. Warning or sanctioning workers who refuse pandemic deployment or speak up about worker and patient safety is associated with lower POS and should be avoided. We also found that high degrees of POS are associated with lower rates of adverse outcomes. So, by implementing the tangible support policies positively associated with POS and avoiding punitive ones, healthcare organizations may be able to reduce adverse mental health outcomes and attrition among their physicians.